COMUNICAÇÃO ESTRATÉGICA DE IES ATRAVÉS DO HANDEBOL DE ALTO RENDIMENTO - SAAR, JEFFERSON FERREIRA (2016)
The doctoral thesis discusses how the Methodist University of São Paulo (UMESP) and the University of Taubaté (UNITAU) using the high performance sport as a means of strategic divulgation. The study shows what is the relationship between the institutional and market communication of the universities and the high performance handball. The thesis presents the communication tools used by UMESP and UNITAU to publicize its sponsorship activities and evaluates the communication flow of marketers universities with sports managers handball. The comparison between universities gave up the use of research method of 'multiple case studies'. The documentary research and literature were used for the theoretical construction work. Data from the study subjects were collected by using the interview technique, those that adopted the characteristic 'semi-structured' with open questions and script use. It was concluded that the UMESP and UNITAU universities bit explore the victorious image of high performance handball investing as a strategic means of divulgation.